Spontaneous Resolution of Subretinal Hemorrhage Secondary to Choroidal Osteoma Unassociated with Choroidal Neovascularization - Mehmet Talay Koylu; Gokcen Gokce; Yusuf Uysal; Ali Hakan Durukan (Case Reports in Ophthalmological Medicine)
Choroidal osteoma is a rare benign intraocular tumor composed of calcification throughout the choroid. Various treatment modalities are available according to location of the tumor and the cause of the visual distortion. We report herein a 30-year-old male who was referred to our hospital with acute blurred vision as a result of the subretinal hemorrhage from choroidal osteoma. We ruled out the presence of CNV and observation was preferred and we prevented unnecessary treatment attempts as spontaneous recovery is the easiest and safest way.